A STUDY ON UTILIZATION OF ANTENATAL CARE SERVICES IN THE URBAN SLUMS OF BHOPAL, MADHYA PRADESH (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Despite national gains in antenatal care (ANC) coverage, women in urban slums remain vulnerable to gaps in service utilization and quality. Slum-specific evidence from Bhopal has been scarce. This study assessed ANC utilization, its pattern, associated factors, and reasons for non-use among women in Bhopal’s urban slums. Methods: A community-based cross-sectional study was conducted over three months. A total of 410 married women aged 20 years and above who had delivered their last child within the previous one year and residing in the selected slums were interviewed. A structured, pre-tested questionnaire captured socio-demographic details, ANC visits, timing, and place of care, iron-folic acid (IFA) intake, Tetanus and Diphtheria (TD) immunisation, and barriers. Data were analysed using SPSS 20.0, with chi-square tests for associations. Results: Almost all women (96.3%) had at least one ANC check‑up; 63.5% made four or more visits and 74.2% booked in the first trimester. Government facilities were the main source of care (60.3%). IFA consumption for the recommended 100 or more days was only 44.4%, with forgetfulness and side effects as leading reasons. TT coverage was substantially higher (85.6% with two doses or booster). Maternal education was the sole factor significantly associated with adequate ANC (71% among women with secondary or higher education vs. 51% among those with less education; p